1988
DOI: 10.1083/jcb.106.5.1475
|View full text |Cite
|
Sign up to set email alerts
|

Site of addition of N-acetyl-galactosamine to the E1 glycoprotein of mouse hepatitis virus-A59.

Abstract: Abstract. By pulse-chase labeling with [35S]methionine and long-term labeling with 3H-sugars, the E1 glycoprotein of coronavirus MHV-A59 has been shown to acquire O-linked oligosaccharides in a two-step process. About 10 min after synthesis of the E1 protein, N-acetyl-galactosamine was added. This was followed ~10 min later by the addition of both galactose and sialic acid to give the mature oligosaccharides. This sequence of additions was confirmed by analyzing the 3H-labeled oligosaccharides bound to each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
166
0
2

Year Published

1989
1989
2002
2002

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(177 citation statements)
references
References 59 publications
9
166
0
2
Order By: Relevance
“…poorly (Baenziger & Fiete, 1979). The initial sugar of Olinked glycans is added in the ER (Pathak et al, 1988;Tooze et al, 1988). It has recently been shown that E2, but not E 1, contains O-linked glycans (Lundstr6m et al, 1991 ;; in agreement with this, we found that E2, but not E 1, bound to the O-glycan-specific lectin Jacalin (not shown).…”
Section: E2 Is Required For Transport Of E1 To the Golgi Apparatus Busupporting
confidence: 75%
“…poorly (Baenziger & Fiete, 1979). The initial sugar of Olinked glycans is added in the ER (Pathak et al, 1988;Tooze et al, 1988). It has recently been shown that E2, but not E 1, contains O-linked glycans (Lundstr6m et al, 1991 ;; in agreement with this, we found that E2, but not E 1, bound to the O-glycan-specific lectin Jacalin (not shown).…”
Section: E2 Is Required For Transport Of E1 To the Golgi Apparatus Busupporting
confidence: 75%
“…Morphological (43,44,49) and biochemical (3,50,54) (44,45), consistent with the possibility that HA was in the intermediate compartment since it is unlikely that HA reached the cis-Golgi. Vesicles containing HA and p58 were not a collapsed form of the ER caused by the mutation in V.24.1 cells because the morphology of the ER was normal as assessed by staining for the ER proteins BiP and ribophorin II.…”
Section: The Intermediate Compartmentmentioning
confidence: 53%
“…The partial sensitivity of O-glycosylation to BFA, in contrast to its complete sensitivity to monensin, indicates that O-glycosylation of the G protein initiates in the trans-Golgi compartment. As noted elsewhere (Tooze et al, 1988;Collins, 1990; and references therein), the intracellular compartment(s) in which Olinked sugars are added can vary in a protein-specific and cell-specific fashion; for some proteins O-glycosylation has been reported to begin in pre-Golgi or earlyGolgi compartments whereas other proteins resemble the G protein in being O-glycosylated in more distal compartment(s) of the exocytic pathway.…”
Section: Discussionmentioning
confidence: 99%